Effects of grazing management and cattle on aquatic habitat use by the anuran pseudopaludicola mystacalis in agro-savannah landscapes - Pelinson, Rodolfo M. [UNESP]; Garey, Michel V.; Rossa-Feres, Denise C. [UNESP] (Public Library of Science (PLoS), 2016)
Because of their strong dependence on the environment, the spatial distribution of pond-breeding amphibians can be greatly influenced by anthropogenic habitat alteration. In some agricultural landscapes in Brazil, the anuran Pseudopaludicola mystacalis appears to be highly influenced by land use. Because adult males and tadpoles of this species are usually found in marshy areas with cattle hoof prints, we hypothesized that P. mystacalis preferentially occupies aquatic habitats with marshy areas that are trampled by cattle. To test our hypothesis, we assessed whether the occurrence of P. mystacalis is associated with the presence of cattle and trampled marshy areas, and which environmental features best explain the spatial distribution and abundance of P. mystacalis. To do so, we sampled 38 aquatic habitats in an area intensely used for livestock in southeastern Brazil. We found that the presence of cattle and trampled marshy areas in aquatic habitats are positively associated to P. mystacalis occurrence. Additionally, the abundance of calling males is better predicted by variables of landscape and local habitat structure. Specifically, the size of trampled marshy areas and the proportion of herbaceous vegetation within the aquatic habitat are positively associated with abundance, while distance to nearest aquatic habitat are negatively associated with abundance of calling males. All three of these variables can be directly or indirectly linked to the presence of cattle or grazing management. Therefore, this work shows evidence that Pseudopaludicola mystacalis is positively influenced by grazing management with cattle, and draws attention to other unknown potential consequences of different land use to fresh water diversity.